The association between allostatic load and brain: A systematic review - Lenart-Bugla, Marta; Szcześniak, Dorota; Bugla, Błażej; Kowalski, Krzysztof; Niwa, Saya; Rymaszewska, Joanna; Misiak, Błażej (Psychoneuroendocrinology, 2022)
Allostatic load (AL) refers to prolonged dysregulation related to chronic stress that affects brain regions such as the hippocampus, amygdala, and prefrontal cortex (PFC). Higher levels of AL have been associated with poor health outcomes, including psychiatric disorders, cognitive decline, and chronic somatic conditions. However, still little is known about the relationship between AL and the brain, and the mechanisms explaining the damaging effects of stress-related biological dysregulations. Therefore, we aimed to perform a systematic review of studies investigating the association of the AL index with brain structure and functioning in adult populations. PubMed/MEDLINE, CINAHL, Academic Search Complete and Web of Science were searched from their inception until August, 9th 2021. A total of 13 studies were included in the qualitative synthesis. There was a high between-study heterogeneity with respect to the methods used to calculate the AL index and brain parameters. All studies confirmed the associations between a higher AL index and alterations in various brain areas, especially: 1) the hippocampus, white matter volume, gray matter volume, and density in the older adults; 2) the cortex, fornix, hippocampus and choroid plexus in patients with schizophrenia spectrum disorders; and 3) whole-brain white matter tracts, cortical gray matter volume, and cortical thickness in overweight subjects. Overall, the findings of this systematic review imply that an elevated AL index might be associated with various neurostructural and neurofunctional alterations. Some of these associations may appear regardless of clinical or non-clinical populations being investigated (e.g., white matter tracts), whereas others may appear in specific populations (e.g., cortical thinning in overweight/obesity and schizophrenia spectrum disorders). However, additional studies utilizing a consistent approach to calculating the AL index are needed to extend these findings and indicate populations that are most vulnerable to the damaging effects of AL. •Elevated allostatic load (AL) might be related to brain alterations in adulthood.•In schizophrenia, AL correlates with larger choroid plexus and fornix alterations.•Reduced hippocampal volume is related to higher AL in schizophrenia and late life.•AL is related to cortical thinning in overweight/obesity.